Differentiating aspects of product innovation processes in the food industry: An exploratory study on New Zealand. Issue 8 (29th July 2014) - Sanaullah Khan, Rao; Vincent Grigor, John; G. Win, Alan; Boland, Mike
Abstract : Purpose: – The purpose of this paper is to sketch a comparative account of NPD approaches between registered New Zealand food companies that are doing some sort of functional foods (FF) development (Group 1) and those that are not (Group 2); to generate a better understanding of differences and commonalities in their NPD approaches from resource-based view of competitive advantage. Design/methodology/approach: – This paper opted an exploratory approach using a quantitative survey across food manufacturing companies in New Zealand. The primary foci of this empirical investigation were: orientation towards the NPD, innovation processes, collaborative NPD links and routes to commercialisation. Findings: – The results (based on a 22 per cent response rate) show a significant difference ( p <0.05) in the aims and mode of NPD between Groups 1 and 2. Further it was observed that food companies in Group 1 have significantly ( p <0.05) more diverse external collaborations with broader aims to collaborate, in comparison with food companies in Group 2. Research limitations/implications: – This study was conducted in New Zealand and thus generalisability of the findings may have to be interpreted carefully. Practical implications: – The traditional NPD approach (independent and closed NPD), with loose intellectual property protection practices, dominates the food manufacturing industry in New Zealand. Research-oriented collaborations need to be strengthened in their scope and content to develop the innovative capabilities and capacities of small and medium enterprises (SME's) within future value-added food productions. Originality/value: – This research provides the comparative narration of innovation process of food manufacturing companies with reference to FFs development.